Risk of bias and reporting completeness of randomised controlled trials in burn care: protocol for a systematic review. Issue 12 (18th December 2019) - Young, Amber; Reeves, Barnaby C; Cheng, Hung-Yuan; Wasiak, Jason; Muir, Duncan; Davies, Anna; Blazeby, Jane
Abstract : Introduction: Burn care represents a healthcare and economic burden to patients internationally. Choice of the most clinically effective treatment strategies requires evidence which is best obtained through high-quality randomised controlled trials (RCT). The number of published RCTs of burn care is increasing. However, trial quality and reporting standards are unclear. This study will assess the risk of bias and adequacy of reporting in recent burn care RCTs using tools endorsed by the Cochrane Collaboration. Methods and analysis: A systematic literature review will be undertaken, assessing parallel group RCTs evaluating therapeutic interventions for patients with cutaneous burns. Literature searches will use Ovid Medline, Ovid Embase, Web of Science and the Cochrane Library. Separate searches for each database will include medical subject heading and free text terms including 'burn', 'scald', 'thermal injury' and 'RCT'. Two reviewers will independently assess each study for inclusion. Risk of bias (RoB) will be assessed with the revised tool (RoB 2) and reporting completeness with the CONsolidated Standards of Reporting Trials (CONSORT) 2010 guidelines. We will report a narrative synthesis of all studies, including domain specific, and overall risk of bias for the primary outcome of each trial. Inter-rater agreement for RoB 2 will be reported using Fleiss's Kappa. For adherence to the CONSORT guidelines, we will generate a completeness of reporting index for the ﬁve domains. Ethics and dissemination: No ethics approval is required because published documents will be used. Findings of the study will be disseminated in a peer-reviewed journal and presented at conferences. PROSPERO registration number: CRD42018111020.